Neo-Naturalism, Conciliatory Explanations, and Spatiotemporal Surprises - Awret, Uziel (Frontiers in Psychology, 2019)
Some materialists believe that physics is rich enough to bridge Levin’s Explanatory Gap, while others believe that it is not. Here I promote an intermediate position holding that physics is rich enough to explain why this gap seems more intractable than similar inter-theoretic explanatory gaps, without providing a full-blown “physical” explanation of consciousness. At a minimum, such an approach needs to explore the prospects of empirical discoveries that can diminish the power of arguments like Chalmers’s “conceivability argument” and Jackson’s “knowledge argument.” While not an easy task, recent advances in the physics of spacetime and information convince us that these prospects are not poor. The empirical bent of this approach and its affinity to the theory-neutral meta-problem of consciousness suggests framing it as a naturalist theory of mind seeking to situate or make room for consciousness within our great naturalist system. However, the reliance of this approach on recent (re)conceptions of time and information pulls the carpet out from underneath essential concepts like concreteness and causation, thus demanding a radically reconfigured naturalism, or neo- naturalism. The question that will frame this discussion is, “What could possibly count as an empirical fact that can help naturalize consciousness?”